ANALISIS PENGETAHUAN DAN SIKAP WISATAWAN TERHADAP POTENSI BENCANA DI DESTINASI WISATA DESA RINDU HATI KABUPATEN BENGKULU TENGAH - Munandar, Aries; Widiastuti, Wahyu (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2022)
Bengkulu Province has many potential tourism objects, but Bengkulu Province is also a disaster-prone area, so that tourist objects will automatically become disaster-prone tourist objects. Several forms of natural events that can be a threat to disasters for tourist attraction areas are earthquakes, tsunamis, landslides, flash floods, hurricanes and tidal waves (Munandar, 2015). To reduce casualties, visitors should know the threat of disasters that could potentially occur in a tourist spot. The research question is: "How are the knowledge and attitudes of tourists towards potential disasters in the tourist destination of Rindu Hati Village, Central Bengkulu Regency?" This study was designed as a qualitative research with an exploratory design. The main informants were 200 respondents who were randomly selected from the visitors to the tourist attractions. Supporting informants are village officials and managers of the tourism object concerned. The results show that the majority of visitors already know the potential for disasters at these tourist attractions, because apart from having visited this tourist attraction before, they also understand the character of areas prone to earthquakes, river areas prone to flash floods and landslides, and heavy currents. which can bring drift. Based on the results of this study, it can be conceptually concluded that although there is a potential disaster, because the threat from the potential disaster according to visitors can already be identified and mitigated, it does not affect their enthusiasm to continue traveling in that place.